A facile synthesis of Fe3O4/nitrogen-doped carbon hybrid nanofibers as a robust peroxidase-like catalyst for the sensitive colorimetric detection of ascorbic acid. Issue 27 (4th July 2017) - Jiang, Yanzhou; Song, Na; Wang, Ce; Pinna, Nicola; Lu, Xiaofeng
Abstract : We describe a facile synthesis of Fe3 O4 /nitrogen-doped carbon hybrid nanofibers as a robust peroxidase-like catalyst for the sensitive colorimetric detection of ascorbic acid. Abstract : In recent years, the fabrication of functional nanostructures with multicomponents for a variety of novel biosensors has received considerable attention due to their synergistic improved sensitivity. Herein, we report a facile approach for the preparation of Fe3 O4 /nitrogen-doped carbon (Fe3 O4 /N–C) hybrid nanofibers, and construct a sensing platform for the sensitive colorimetric detection of H2 O2 and ascorbic acid (AA). During the synthetic process, a discontinuous layer of polypyrrole (PPy) is first polymerized in situ on the surface of the α-Fe2 O3 nanofibers under hydrothermal reaction using α-Fe2 O3 nanofibers as both a template and an oxidant. Then the prepared α-Fe2 O3 /PPy nanofibers are converted into Fe3 O4 /N–C hybrid nanofibers through pyrolysis with a thermochemical reduction process. The resulting Fe3 O4 /N–C hybrid nanofibers are used as a novel peroxidase mimic towards the oxidation of 3, 3, 5, 5-tetramethylbenzidine (TMB) in the presence of H2 O2, with a superior catalytic activity over individual α-Fe2 O3 nanofibers, α-Fe2 O3 /PPy nanofibers, Fe3 O4 /C nanofibers, and commercial Fe3 O4 nanoparticles. Based on the high peroxidase-like activity of Fe3 O4 /N–C hybrid nanofibers, a sensing platform for the colorimetric detection of AA is developed. A good linear relationship from 0 to 50 μM and a detection limit of 0.04 μM are achieved. This work offers a new method for the preparation of Fe3 O4 /N–C hybrid nanofibers and presents new potential applications in biosensing, medical diagnostics and environmental monitoring.